SQl/DS Tool Support and Third-Party Vendors: What's on the Horizon? - Eaton, Roger G. (My University, 2016)
In the beginning, there was SQL/DS. Developed by IBM as an expansion to Sequel (a derivative of its first relational DBMS effort, System R), it served VSE/SP installations, and later, VM/SP. Its reception was lukewarm. SQL/DS was slow out of the gate, perhaps due to the lack of complimentary products. Managing an SQL/DS database requires more set-up than the standard VSAM delete and define. Although the number of SQL/OS licenses has reached 7,500 to 8,000, few shops have given SQL/DS the nod as their "first team" data structure.
Citation: Eaton, R. (1992). SQl/DS Tool Support and Third-Party Vendors: What's on the Horizon? DATABASE Programming & Design, 5(10) 75-76
Keywords: SQL/DS; Relational Databases; DBMS; Data Definition Language